2022
DOI: 10.3389/fsoc.2022.1041435
|View full text |Cite
|
Sign up to set email alerts
|

Khaled Hosseini's women as modern archetypes: A study of obedient, resistant and empowered Afghan women

Abstract: This article focuses on Khaled Hosseini's use of the analogy of women as obedient, resistant, and empowered as modern archetypes who learn of the gendered oppression that works through their bodies. Khaled Hosseini, through his writings, lends voice and offers moral encouragement to women by crafting resistant, rebellious, empowered, and strong female characters. With theoretical support from Johnson's Patriarchal Terrorism and Spivak's Can the subaltern speak, this article traces how Hosseini interrogates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Thus, the resilience of women and Afghanistan in the face of oppression and hostility become equally important themes in Hosseini's writing. According to this study, Hosseini links the war on terror, foreign invasions, and the Taliban's rule in Afghanistan to issues affecting Afghan women, such as tradition and modernity, women and Islam, mother and daughter relationships, resistance and rebellion, and their quest for change and empowerment (Imran, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the resilience of women and Afghanistan in the face of oppression and hostility become equally important themes in Hosseini's writing. According to this study, Hosseini links the war on terror, foreign invasions, and the Taliban's rule in Afghanistan to issues affecting Afghan women, such as tradition and modernity, women and Islam, mother and daughter relationships, resistance and rebellion, and their quest for change and empowerment (Imran, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While there have been numerous studies conducted on the issue of women's struggle against patriarchy as demonstrated by studies conducted by Imran (2022), Fadhilah & Handayani (2022), Fauzia & Rahayu (2019), Das & Rai (2022), there has been a gap in the exploration of women's struggle to fight back patriarchal regime. Dancing in The Mosque by Homeira Qaderi is one such piece that has not been frequently studied in academia, particularly in the context of women's struggle.…”
Section: Introductionmentioning
confidence: 99%
“…While A Thousand Splendid Suns focuses more on the harsh realities of life under Taliban rule (Subedi, 2023), The Kite Runner stands out in its profound portrayal of intercultural interactions and conflicts within Afghan society, making it a focal point in discussions about multiculturalism in literature. It is Hosseini's (2003) debut novel, which marked his literary career has garnered immense admiration for its historical and ethnographic importance (Imran & Ismail, 2022), becoming a bestseller in the USA and receiving acclaim as the reading group book of the year (Miswari, 2018). It spans a broader timeline, covering periods before and after the fall of the Taliban regime, providing a nuanced perspective on the complexities within Afghan society (Agnello et al, 2009).…”
Section: Introductionmentioning
confidence: 99%